Gambaran Status Gizi Pada Pasien Tuberkulosis Paru (TB Paru) Usia 0-5 Tahun yang Menjalani Rawat Jalan di Poli Anak RSUD Cut Meutia Aceh Utara Tahun 2022 - Mardiati Mardiati; Harida Fitri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Tuberculosis (TB) is an infectious disease caused by the germ Mycobacterium tuberculosis, which can attack various organs, especially the lungs. This disease if not treated or treatment until complete it will cause dangerous complications until death. Objective: To determine the picture of nutritional status in Pulmonary TB patients aged 0-5 years who undergo outpatient treatment at the Children's Poly of RSUD Cut Meutia North Aceh in 2022. Method: This study is a descriptive research conducted from September 1, 2021 to August 31, 2022. Results: The age of respondents diagnosed with Pulmonary TB was at most 13-24 months and 49-60 months respectively (25%) with the highest sex of respondents being men (55%). Nutritional Status in the measurement of BB / U is the most with normal weight (50%), TB / U index obtained normal height (60%), BB / TB index and BMI / U have the most good nutritional status (65%). Conclusion: Variations in the nutritional status of pulmonary TB patients were obtained at the Children's Poly of RSUD Cut Meutia Aceh